Impact of Covid-19 Pandemic on Students Learning Outcomes in Universities in Osun State, Nigeria - Abanikannda Mutahir Oluwafemi; Akinola Oluwatoyin Temiloluwa (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
The study investigated the impact of COVID-19 pandemic in the process of education of students from Osun Universities in Nigeria. The study is a descriptive one; a sample of 360 students from the universities in Osun State formed the participants for the study. The instrument for data collection was a questionnaire structured by the researcher for data collection and its reliability level was 0.83. Data collected were analysed, using descriptive statistics, specifically mean, standard deviation, frequency counts and Person Product Moment Correction (PPMC). The findings of the study revealed that COVID-19 pandemic has negative effect on students' learning outcomes from Osun State in Nigeria. The study revealed that there is no significant difference in the learning outcomes of students, depending on the type of school. Finally, the findings revealed that gender does not significantly differentiate the learning outcomes of the respondent students in Osun, Nigeria, under the COVID-19 pandemic situation. The following recommendations were made: government should consider the need to build good schools and equip them with modern digital facilities; government should ensure inclusion of online teaching such as integrated digital learning platforms, video lessons, broadcasting through radio and TV etc. to supplement the normal classroom teaching; educators as well as students must be trained on how to handle and use online educational devices; educators must spend quality time to prepare and make their lessons creative, interactive, relevant, student-centred and group-based; parents should pay personal attention to monitor and supervise their children until they adapt to online teaching environment; and government aid is needed in terms of investing in educational tools of the future alongside a total revamp of the educational sector as well as reforms in the national curriculum post-pandemic. Keywords: COVID-19, pandemic, learning outcomes, universities, school type Wpływ pandemii Covid-19 na proces edukacji studentów na uniwersytetach Osun w Nigerii W artykule przedstawiono wyniki badania dotyczącego wpływu pandemii COVID-19 na osiągnięcia w nauce studentów uniwersytetów w Osun w Nigerii. Badanie miało charakter opisowy. Wzięło w nim udział 360 studentów z uniwersytetów w stanie Osun. Narzędzie do zbierania danych stanowił opracowany przez badacza kwestionariusz, którego poziom rzetelności wyniósł 0,83. Zebrane dane zostały przeanalizowane przy użyciu statystyk opisowych, w szczególności średniej, odchylenia standardowego, liczby częstości i korekcji momentu produktu osoby (PPMC). Wyniki dowiodły, że pandemia COVID-19 ma negatywny wpływ na to, jakie rezultaty osiągają studenci w stanie Osun w Nigerii. Wykazały również brak znaczącej różnicy w wynikach uzyskiwanych przez studentów w zależności od typu szkoły, jak również płci. Przedstawiono następujące rekomendacje: rząd powinien dostrzegać potrzebę budowania dobrych szkół i wyposażania ich w nowoczesne urządzenia cyfrowe oraz zapewnić włączenie nauczania online, takiego jak zintegrowane cyfrowe platformy edukacyjne, lekcje wideo, nadawanie przez radio i telewizję itp. w celu uzupełnienia nauczania w klasie; nauczyciele i uczniowie muszą być przeszkoleni w zakresie obsługi i korzystania z urządzeń edukacyjnych online; nauczyciele są obowiązani poświęcić czas na przygotowanie i sprawić, aby ich lekcje były kreatywne, interaktywne, zorientowane na ucznia i oparte na grupie; do obowiązków rodziców należy poświęcanie uwagi monitorowaniu i nadzorowaniu dzieci, dopóki nie przystosują się do środowiska nauczania online, a pomoc rządu jest potrzebna w zakresie inwestowania w narzędzia edukacyjne przyszłości wraz z całkowitą przebudową sektora edukacyjnego w postaci reform krajowego programu nauczania po pandemii.